1990
DOI: 10.1152/jappl.1990.69.2.504
|View full text |Cite
|
Sign up to set email alerts
|

Rat soleus muscle ultrastructure after hindlimb suspension

Abstract: The aim of the present investigation was to determine, by quantitative electron microscopy, the effects of a 5-wk tail-suspension period on rat soleus muscle ultrastructure. A marked decline (-60%) in muscle mass occurred. The mean fiber cross-sectional area decreased to a greater extent (-75%) than the capillary-to-fiber ratio (-37%), leading to a higher capillary density (+148%) after hypokinesia. The total mitochondrial volume density remained unchanged, whereas the volume density of myofibrils was slightly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
49
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 0 publications
9
49
0
Order By: Relevance
“…To our knowledge, this is the first study to show that decrements in skeletal muscle mitochondria, caused by denervation, can be attenuated by prior chronic stimulation. Furthermore, we were not overly surprised by the preferential reduction in SS mitochondria in response to denervation, as this subfraction has been shown to have a heightened sensitivity to alterations in muscular activity (11,16).…”
Section: Discussionmentioning
confidence: 80%
“…To our knowledge, this is the first study to show that decrements in skeletal muscle mitochondria, caused by denervation, can be attenuated by prior chronic stimulation. Furthermore, we were not overly surprised by the preferential reduction in SS mitochondria in response to denervation, as this subfraction has been shown to have a heightened sensitivity to alterations in muscular activity (11,16).…”
Section: Discussionmentioning
confidence: 80%
“…diameter (16,36). Desplanches et al (7) reported that hindlimb suspension of rats for 5 wk resulted in a decrease of 37% in the C/F ratio but an increase of 48% in capillary density. HU causes atrophy of skeletal muscle fibers, reducing the muscle mass (7,28).…”
Section: Discussionmentioning
confidence: 99%
“…Desplanches et al (7) reported that hindlimb suspension of rats for 5 wk resulted in a decrease of 37% in the C/F ratio but an increase of 48% in capillary density. HU causes atrophy of skeletal muscle fibers, reducing the muscle mass (7,28). If the degree of muscle atrophy is greater than that of capillary regression, the capillary density should increase despite the decrease in the C/F ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported decreases in number of mitochondria as well as the appearance of mitochondrial swelling in HU rats [4,18]. In contrast, the levels of citrate synthase activity, as well as the levels of -hydroxyacyl CoA dehydrogenase, increased in the gastrocnemius, semitendinosus and cardiac muscles in hibernating golden-mantled ground squirrels or loading rats [17,27].…”
Section: Discussionmentioning
confidence: 79%